Steven’s Johnson Syndrome: A Case Report and Application of Lydia E. Hall’s Core, Care, Cure, Theory with Nursing Process Approach - Chetan Ramesh Sangati; Ananda Kudari, (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2019)
Steven’s–Johnson syndrome is abbreviated as SJS and is also medically recognized or it is also known as Lyell's syndrome, toxic epidermal necrolysis, and Stevens-Johnson syndrome toxic epidermal necrolysis spectrum. It's usually due to the reaction of medication or an infection. Later, it begins with flu-like symptoms, like Fever, unexplained widespread skin pain, a red or purple skin rash that spreads, blisters on your skin and the mucous membranes. To find out the Steven’s-Johnson syndrome clinical systemic examination is must, in which skin biopsy is important diagnostic tool to find the cause along with skin or oral culture as well as imaging study which is depending on the client symptoms and also blood investigation have legendary role to find the Steven’s-Johnson syndrome. If it was caused by a medication client or victim should permanently avoid those drugs and supportive care should be taken for the client.